Factors that influence organizational commitment of employees at Felda Global Ventures Holdings Berhad / Nurul Masturah Mahayuddin - Mahayuddin, Nurul Masturah (Faculty of Business and Management, 2018)
This research explores the factors that contribute to organizational commitment among employees at Felda Global Ventures Holdings Berhad (FGVHB). The main objective of this research is to identify the factors that influence organizational commitment at FGVHB. Three independent variables are identified, employee empowerment, teamwork and employee training. In order to complete this research, three hypotheses were constructed, focusing on determining the factor that influence organizational commitment. Questionnaire was distributed using non probability sampling that is convenient sampling and a total of 125 questionnaires were distributed with 89 questionnaires were received back. The data obtained were analyzed using SPSS. The findings show that the two variables, organizational commitment and employee training were important in influencing organizational commitment. Thus, two hypotheses failed to reject and one hypotheses are rejected.